Enhancement of the power conversion efficiency for inverted organic photovoltaic devices due to the localized surface plasmonic resonant effect of Au nanoparticles embedded in ZnO nanoparticles. (1st July 2015) - Lee, Yong Hun; Kim, Dae Hun; Lee, Dea Uk; Li, Fushan; Kim, Tae Whan
Abstract: The absorption spectra and input photon-to-converted current efficiency curves showed that Au nanoparticles increased the plasmonic broadband light absorption, thereby enhancing the short-circuit current density of the inverted organic photovoltaic (OPV) cells with a Au–ZnO nanocomposite electron transport layer (ETL). The power conversion efficiency of the inverted OPV cell fabricated with a Au–ZnO nanocomposite ETL was higher by 40% than that of the inverted OPV cell fabricated with a ZnO nanoparticle ETL, which could be attributed to the enhanced photon absorption in the active layer due to the localized surface plasmonic resonance of the Au nanoparticles.